Early manifestations of genetic liability for ADHD, autism and schizophrenia at ages 18 and 24 months - Lucy Riglin; Esther Tobarra‐Sanchez; Evie Stergiakouli; Alexandra Havdahl; Kate Tilling; Michael O'Donovan; Joel Nigg; Kate Langley; Anita Thapar (Wiley, 2022)
Abstract Background ADHD and autism are neurodevelopmental conditions, for which non‐specific precursors or early signs include difficulties with language and motor skills, and differences in temperament in the first and second year of life. These early features have also been linked to later diagnosis of schizophrenia which is widely considered to have neurodevelopmental origins. Given that ADHD, autism and schizophrenia are all highly heritable, we tested the hypothesis that in the general population, measures of toddler language development, motor development and temperament are associated with genetic liability to ADHD, autism and/or schizophrenia. Methods Data were analysed from the Avon Longitudinal Study of Parents and Children (ALSPAC) which included motor development scores at age 18 months and language development and temperament scores at age 24 months (N = 7498). Genetic liability was indexed by polygenic risk scores (PGS) for ADHD, autism and schizophrenia. Results ADHD PGS were associated with specific temperament scales (higher activity β = 0.07, 95% CI = 0.04, 0.09 and lower withdrawal β = −0.05, 95% CI = −0.07, −0.02) as well as better gross motor scores (β = 0.04, 95% CI = 0.01, 0.06). Schizophrenia PGS were associated with one specific temperament scale (negative mood β = 0.04, 95% CI = 0.02, 0.07). We did not find strong evidence of association of autism PGS with any of the toddler measures; there was also not strong evidence of association with motor or language delays for any of the PGS. Conclusions This study suggests that some specific aspects of early temperament and gross motor differences in the general population could represent part of the early manifestation of genetic liability to neurodevelopmental conditions.